ELECTRONIC MEDICAL RECORD INFORMATION SYSTEM DESIGN TO SUPPORT THE REPORTING OF COMPLETENESS OF BPJS PATIENT MEDICAL RECORDS WITH EXTREME PROGRAMMING METHOD - Kustiani, Rini; Syahidin, Yuda; Yunengsih, Yuyun (Jurnal Teknik Informatika (Jutif), 2024)
This research was conducted considering that there are still many problems regarding the completeness of medical records, especially for BPJS patients. The number of incomplete filling of medical records and the inaccuracies in the medical record completeness analysis report. The inaccuracy of the data causes miscommunication between doctors and medical record officers. Also, notes about the incompleteness of medical records that doctors need to complete are still done conventionally so they are prone to being lost and unreadable. This study aims to design an electronic medical record information system design to support the reporting of medical record completeness. The research method used is qualitative and data obtained from observations, interviews, literature studies, and software development with Extreme Programming method. This research produces a system that can help officers and doctors to access data on the results of BPJS patient medical record analysis, including information about incompleteness. This can prevent data inaccuracies and ensure officers and doctors know the latest information about the completeness of medical records as a requirement for BPJS claims. This system can also help improve the performance of officers in processing medical record analysis data and produce reports that are more accurate and efficient than the system used previously.